2010
DOI: 10.1088/0960-1317/21/1/015002
|View full text |Cite
|
Sign up to set email alerts
|

Development rate of PMMA exposed to synchrotron x-ray radiation for LIGA applications

Abstract: This paper investigates the development rate of poly(methyl methacrylate) (PMMA) after it is exposed to synchrotron x-ray radiation. The x-ray exposures were performed at both Synchrotron Radiation Center and Brookhaven National Laboratories. The development rate of PMMA in a variety of developers was measured as a function of absorbed x-ray dose (J cm −3 ). The development rate of four different types of PMMA was investigated: unexposed 950k PMMA, Cryo GMS PMMA, Goodfellow CQ PMMA, and Crosslinked PMMA. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…% 2-aminoethanol, and 15 vol. % deionized water) [31,33]. Two kinds of PMMA plates with different thicknesses were used.…”
Section: Methodsmentioning
confidence: 99%
“…% 2-aminoethanol, and 15 vol. % deionized water) [31,33]. Two kinds of PMMA plates with different thicknesses were used.…”
Section: Methodsmentioning
confidence: 99%
“…It consisted of 60% 2-(2-butoxy-ethoxy)ethanol, 20% tetra-hydro-1, 4-oxazine, 5% 2-aminoethanol-1 and 15% water by volume. These materials were known to work well for LIGA and were good enough for controlling surface roughness [24]. The exposed region was far from the edge to minimize stress effects and PMMA samples were developed immediately after the exposure process to avoid any possible cracks [24,29].…”
Section: Methodsmentioning
confidence: 99%
“…These materials were known to work well for LIGA and were good enough for controlling surface roughness [24]. The exposed region was far from the edge to minimize stress effects and PMMA samples were developed immediately after the exposure process to avoid any possible cracks [24,29]. The developing temperature was maintained at 40 • C in a temperature-controlled bath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the development conditions after exposure also play an important role in affecting the aspect ratio of nano-grating. Many factors affecting the development efficiency of photoresist have been investigated by Mcnamara et al [41]. It was concluded that the effect of synchrotron radiation spectra on the development rate is negligible when the x-ray dose and development temperature are kept constant.…”
Section: Introductionmentioning
confidence: 99%